Simply keto - Ryan, Suzanne (Blogger) (Las Vegas : Victory Belt Publishing Inc., 2017)
Simply Keto is a practical and easy-to-understand guide to the ketogenic diet with more than 100 low-carb, high fat recipes and advice from popular blogger Suzanne Ryan.
All about keto -- Ketogenic food and shopping lists -- Recipes -- 30-day meal plan -- Taking keto on the road.
Includes allergen and general indexes.
Keywords: Ketogenic diet; Reducing diets; Low-carbohydrate diet; Cookbooks; Cookbooks; Cookbooks